The Work of Art in a Digital Age: Art, Technology and Globalisation - Langdon, Melissa; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book explores digital artists$1 (Barticulations of globalization. Digital artworks from around the world are examined in terms of how they both express and simulate globalization$1 (Bs impacts through immersive, participatory and interactive technologies. The author highlights some of the problems with macro and categorical approaches to the study of globalization and presents new ways of seeing the phenomenon as a series of processes and flows that are individually experienced and expressed. Instead of providing a macro analysis of large-scale political and economic processes, the book offers imaginative new ways of knowing and understanding globalization as a series of micro affects. Digital art is explored in terms of how it re-centers articulations of globalization around individual experiences and offers new ways of accessing a complex topic often expressed in general and intangible terms. The Work of Art in a Digital Age: Art, Technology and Globalization is analytic and accessible, with material that is of interest to a range of researchers from different disciplines. Students studying digital art, film, globalization, cultural studies or digital media trends will also find the content fascinating.s
Introduction: Towards New Understandings -- Chapter 1: Digital Art and Cultural Commentary -- Chapter 2: Globalization and Digital Art -- Chapter 3: Digital Art and Political Revolt -- Chapter 4: Global Space, Time and Speed: T Visionarium II and Beijing Accelerator -- Chapter 5: Metropolis: Imagining the Global City -- Chapter 6: In the Line of Flight: Changing Practices in Digital Art -- Chapter 7: Digital Art and Social Engagement -- Conclusion: Digital Art as a Platform of Articulation.
Keywords: Computer science; Application software; Multimedia systems; Computer Science; Computer Appl. in Arts and Humanities; Media Design; Electronic books